Multiple Myo4 motors enhance ASH1 mRNA transport in Saccharomyces cerevisiae - Chung, Sunglan (The Rockefeller University Press, 2010)
In Saccharomyces cerevisiae, ASH1 mRNA is transported to the bud tip by the class V myosin Myo4. In vivo, Myo4 moves RNA in a rapid and continuous fashion, but in vitro Myo4 is a nonprocessive, monomeric motor that forms a complex with She3. To understand how nonprocessive motors generate continuous transport, we used a novel purification method to show that Myo4, She3, and the RNA-binding protein She2 are the sole major components of an active ribonucleoprotein transport unit. We demonstrate that a single localization element contains multiple copies of Myo4 and a tetramer of She2, which suggests that She2 may recruit multiple motors to an RNA. Furthermore, we show that increasing the number of Myo4–She3 molecules bound to ASH1 RNA in the absence of She2 increases the efficiency of RNA transport to the bud. Our data suggest that multiple, nonprocessive Myo4 motors can generate continuous transport of mRNA to the bud tip.